E2 Site Mutations in S Protein Strongly Affect Hepatitis B Surface Antigen Detection in the Occult Hepatitis B Virus - Wang, Hao; Liao, Fenfang; Xie, Junmo; Gao, Wenbo; Wang, Min; Huang, Jieting; Xu, Ru; Liao, Qiao; Shan, Zhengang; Zheng, Yourong; Rong, Xia; Li, Chengyao; et al. (Frontiers in Microbiology, 2021)
The mechanism of occult hepatitis B infection (OBI) has not yet been fully clarified. Our previous research found that novel OBI related mutation within S protein, E2G, could cause the HBsAg secretion impairment which resulted in intracellular accumulation in OBI of genotype B. Here, to further explore the role of E2 site mutations in the occurrence of OBI, we analyzed these site mutations among 119 OBI strains identified from blood donors. Meanwhile, 109 wild type HBV strains (HBsAg positive/HBV DNA positive) were used as control group. Further to verify the E2 site mutations, two conservative 1.3-fold full-gene expression vectors of HBV genotype B and C (pHBV1.3B and pHBV1.3C) were constructed. Then, the E2 mutant plasmids on the basis of pHBV1.3B or pHBV1.3C were constructed and transfected into HepG2 cells respectively. The extracellular and intracellular HBsAg were analyzed by electrochemical luminescence and cellular Immunohistochemistry. The structural characteristics of S proteins with or without E2 mutations were analyzed using relevant bioinformatic softwares. E2 mutations (E2G/A/V/D) existed in 21.8% (26/119) OBIs, while no E2 mutations were found in the control group. E2G/A/V/D mutations could strongly affect extracellular and intracellular level of HBsAg (P<0.05). Notably, unlike E2G in genotype B which could cause HBsAg intracellular accumulation and secretion decrease (P<0.05), E2G in genotype C could lead to a very significant HBsAg decrease both extracellularly (0.46% vs pHBV1.3C) and intracellularly (11.2% vs pHBV1.3C) (P<0.05). Meanwhile, for E2G/A mutations, the relative intracellular HBsAg (110.7-338.3% vs extracellular) and its fluorescence intensity (1.5-2.4 fold vs with genotype-matched pHBV1.3B/C) were significantly higher (P<0.05). Furthermore, N-terminal signal peptides, with a typical cleavage site for peptidase at position 27 and 28, were exclusively detected in S proteins with secretion-defective mutants (E2G/A). Our findings suggest that: (i) E2G/A/V/D mutations were confirmed to significantly influence the detection of HBsAg, (ii) the underlying mechanism of OBI caused by E2G mutation is quite different between genotype B and genotype C, (iii) E2G/A could produce a N-terminal truncated S protein, which might attribute to the HBsAg secretion impairment in the OBIs.